Implementation of the “CANTIK” (Preventing Anemia with Acupressure Techniques and Consuming Blood Supplement Tablets) in Adolescent Girls to Prevent Stunting - Ida Ayu Anom Rastiti; Ida Ayu Suptika Strisanti (Babali Nursing Research)
Introduction: The study explores the connection between anemia in adolescent girls and the risk of stunting in their future children. To prevent this, researchers developed the CANTIK program, which combines acupressure techniques and iron supplementation. The aim is to evaluate the program's effectiveness in improving hemoglobin levels and preventing anemia in adolescent girls.